5,6-O-isopropylidene-3-C-methyl-D-mannono-1,4-lactone - Curran, L; Jones, N; Jenkinson, S; Watkin, D; Fleet, G (2007)
The relative configuration of the title compound, C10H16O6, was firmly established by X-ray crystallographic analysis. The absolute configuration was determined by the use of 2-C-methyl-d-arabinose as the starting material. The crystal structure exists as hydrogen-bonded sheets lying approximately perpendicular to c. © International Union of Crystallography 2007.